Molecular gel sorbent materials for environmental remediation and wastewater treatment - Lim, Jason Y. C; Goh, Shermin S; Liow, Sing Shy; Xue, Kun; Loh, Xian Jun (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
Molecular gels are promising new classes of materials for the treatment of polluted water owing to their large surface area for pollutant sorption and ease of chemical modification. In recent years, exceptional gel performance in the removal of pollutants such as oil, excess and/or toxic cations and anions, as well as dyes and pharmaceutical products have been reported. However, for them to be used in real-life settings, numerous practical considerations such as gel mechanical properties and recyclability also need to be taken into account. In this review, we highlight key advances in the development of this class of sorbent materials with an emphasis on hydrogels, comprising small molecule supramolecular gelators, polymers and composites comprising graphene/graphene oxide, microorganisms and iron nanoparticles achieved during the last decade. In our 'bottom-up' approach, we emphasise the key design features of each gel material accounting for its target pollutant adsorption characteristics and material properties, together with the most important practical considerations necessary for real-life usage. By putting these into perspective, we hope that this review will stimulate further strategic translational research into practical gel remediators capable of integrating with and complementing existing water treatment technologies. Exciting advances in the last decade regarding the applications of molecular gel sorbent materials for removal of pollutants from wastewater are reviewed, with emphasis on molecular design of the materials and practical considerations.